Histopathological liver findings in patients with hepatocerebral mitochondrial depletion syndrome with defined molecular basis - Pronicki, Maciej; Piekutowska-Abramczuk, Dorota; Rokicki, Dariusz; Iwanicka-Pronicka, Katarzyna; Grajkowska, Wiesława (Polish Journal of Pathology, 2018)
Mitochondrial DNA depletion consisting of the systemic reduction of mtDNA copy number in cells may have a heterogenous genetic basis, resulting from a pathogenic change in the nuclear genes involved in mtDNA synthesis. The mode of inheritance is autosomal recessive. Severe hepatocerebral disease represents one of many different clinical forms of so-called mitochondrial depletion syndrome (MDS). We present the liver histopathology of 13 children who eventually died in the course of hepatocerebral MDS confirmed molecularly, harbouring mutations of DGUOK , MPV17 , and POLG genes. Material comprising eight autopsy and five liver biopsy specimens showed a moderately reproducible pattern of parenchymal damage, which we consider potentially helpful in the differential diagnosis and planning of the diagnostic investigation in families of children who died due to early-onset acute liver failure and encephalopathy.